Male Child Preference for The First Child Decreasing Among Women in Surat City - Thakkar , Dhwanee; Viradiya , Hiral; Shaikh , Nawal; Bansal , RK; Shah , Dhara; Shah , Shashank (National Journal of Community Medicine, 2011)
The systematic undervaluation of women is quite visible in our country through adverse sex ration at birth for girls. The present study attempts to address the desired gender preferences of the first child of couples in Surat city. Randomly selected 270 women were interviewed using a semi structured questioner. It was observed that just below two-thirds (63%) of the respondents had expressed their contentment with either gender choice. Of the remaining the majority had expressed their desire for a male child (22.2%) followed by a female child (14.4%). ‘Ensuring continuation of family name’ was the most cited reason for preferring male as a first child while ‘females are considered as the ‘Laxmi’ of the house’ was the most common reason for favoring female as first child. However, Nearly all of the respondents (98.9%) profess that boys and girls should be given equal rights. At the minimum the study revealed that the people of Surat city are becoming sensitive towards the issue of male child reference or at least adopting a politically correct attitude in public settings.